Long-term outcome of profound hyponatremia: a prospective 12 months follow-up study. Issue 6 (December 2016) - Winzeler, Bettina; Jeanloz, Nica; Nigro, Nicole; Suter-Widmer, Isabelle; Schuetz, Philipp; Arici, Birsen; Bally, Martina; Blum, Claudine; Bock, Andreas; Huber, Andreas; Mueller, Beat; Christ-Crain, Mirjam
Abstract : Background: Hyponatremia is the most common electrolyte abnormality in hospitalized patients and given its impact on mortality and morbidity, a relevant medical condition. Nevertheless, little is known about factors influencing long-term outcome. Methods: This is a prospective observational 12-month follow-up study of patients with profound hyponatremia (≤125 mmol/L) admitted to the emergency department of two tertiary care centers between 2011 and 2013. We analyzed the predictive value of clinical and laboratory parameters regarding the following outcomes: 1-year mortality, rehospitalization and recurrent profound hyponatremia. Results: Median (IQR) initial serum sodium (s-sodium) level of 281 included patients was 120 mmol/L (116–123). During the follow-up period, 58 (20.6%) patients died. The majority (56.2%) were rehospitalized at least once. Recurrent hyponatremia was observed in 42.7%, being profound in 16%. Underlying comorbidities, assessed by the Charlson Comorbidity Index, predicted 1-year mortality (odds ratio (OR) 1.43, 95% confidence interval (CI) 1.25–1.64, P  < 0.001). Furthermore, 's-sodium level at admission' (OR 1.14, 95% CI 1.01–1.29, P  = 0.036) and 'correction of hyponatremia' defined as s-sodium ≥135 mmol/L at discharge were associated with mortality (OR 0.47, 95% CI 0.23–0.94, P  = 0.034). Mortality rate fell with decreasing baseline s-sodium levels and was lower in the hyponatremia category ≤120 mmol/L vs >120 mmol/L (14.8% and 27.8%, P  < 0.01). Patients with s-sodium level ≤120 mmol/L were more likely to have drug-induced hyponatremia, whereas hypervolemic hyponatremia was more common in patients with s-sodium >120 mmol/L. Conclusion: Hyponatremia is associated with a substantial 1-year mortality, recurrence and rehospitalization rate. The positive correlation of s-sodium and mortality emphasizes the importance of the underlying disease, which determines the outcome besides hyponatremia itself.